Sacred ground: pluralism, prejudice, and the promise of America - Eboo Patel (Beacon Press, 2012)
In the more than a decade following the attacks of 9/11, suspicion and animos ity toward America Muslims have increased rather than subsided, with pundits and politicians routinely invoking the specter of Islam as a menacing, deeply anti-America force